Efficacy and safety of noninvasive focused ultrasound for treatment of subcutaneous adiposity in healthy women - Fonseca, Viviane Mancinelli; Campos, Priscila Soares; Certo, Thays Fernanda; de-Faria, Luana Taís; Juliano, Priscila Bianchi; Cintra, Dennys Esper; Eloin Liebano, Richard; da Silva, Caroline [UNESP]; Guidi, Renata Michelini; Sant’Ana, Estela (Taylor & Francis, 2018)
Introduction: In recent years, a new method focused ultrasound (FUS) has been used in the treatment of localized fat. The objectives of this work were to evaluate the efficacy and safety of the FUS in the treatment of abdominal subcutaneous fat. Materials and Methods: Thirty-one healthy women were divided into two groups: G1 (N = 7), 6 sessions, 3 passes, once a week and G2 (N = 23), 10 sessions, 2 passes, twice a week. Outcome measures were reduction of circumference and fat thickness. Safety monitoring included laboratory testing (serum lipids profile and liver function tests) and adverse events were also assessed. Patient satisfaction and tolerance questionnaires were also applied. One patient underwent abdominoplasty and received a single session of FUS 24 h before surgery and a skin sample was collected for histological analysis. Results: The results showed improvement in body contouring and reduction of the thickness of the fat layer observed by ultrasonography in both groups: G1 (P < 0.001) and G2 (P < 0.0001). The histology showed disrupted adipocytes and collapsed membranes 24 h after the FUS treatment. Conclusion: FUS represents an effective and safe treatment for reducing localized adipose tissue by adipocytolysis.
Keywords: adipocyte; adipocytolysis; cavitation; HIFU